2017
DOI: 10.1007/s10597-017-0086-y
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Psychoeducation on the Expressed Emotion and Family Functioning of the Family Members in First-Episode Schizophrenia

Abstract: The aim of this study was to determine the effects of the psychoeducation received by the family members of the patients with first-episode schizophrenia on the expressed emotion (EE) and the family functioning of the family members. This study has a quasi-experimental design with a control group. The sample of the study was 60 family members (30 experimental -30 control) of the patients with first-episode schizophrenia. The experimental group received 9 weeks of psychoeducation as a group. EE and family funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 28 publications
1
11
0
1
Order By: Relevance
“…Among the three proposed WeChat-based mHealth program elements, psychoeducation is the most commonly endorsed mode of intervention by the participants. This finding is consistent with the bulk of literature showing psychoeducation as the predominant and most effective intervention to improve well-being of PLS and their families (Khalil et al, 2019;Oksuz et al, 2017). Evidence shows that psycho-education not only significantly decrease relapse and improve recovery in PLS, but also decrease family burden and improve psychosocial well-beings in family members (Pekkala & Merinder, 2002;Sorrell, 2014).…”
Section: Discussionsupporting
confidence: 89%
“…Among the three proposed WeChat-based mHealth program elements, psychoeducation is the most commonly endorsed mode of intervention by the participants. This finding is consistent with the bulk of literature showing psychoeducation as the predominant and most effective intervention to improve well-being of PLS and their families (Khalil et al, 2019;Oksuz et al, 2017). Evidence shows that psycho-education not only significantly decrease relapse and improve recovery in PLS, but also decrease family burden and improve psychosocial well-beings in family members (Pekkala & Merinder, 2002;Sorrell, 2014).…”
Section: Discussionsupporting
confidence: 89%
“…Örneklem grubunu oluşturan bakım vericilerin hastalarının kronik süreçte olmalarına rağmen bakım vericilere yapılan psikoeğitimin DD'ye etkili olduğu belirlenmiştir. Oysa yapılan çalışmalarda akut dönemde olan hastaların bakım vericilerine yapılan psikoeğitimin etkisinin daha fazla olduğu bildirilmektedir (8,(52)(53)(54)(55) kazanılması ve inatçı belirtilerle başa çıkma konusunda alternatif yolların öğrenilmesine katkıda bulunduğu görülmektedir. Ayrıca psikoeğitim girişimi bakım vericilerin bakım verdikleri hastalarının tedaviye uyum sağlamalarını arttırmakta, ruhsal bozukluğa ilişkin belirti ve bulgularla nasıl baş edeceklerine katkı sağlamakta gibi görülmektedir.…”
Section: Introductionunclassified
“…On the care focused on caregivers of people with mental disorders, psycho-education and support groups appear to be effective interventions. International studies on conducting psycho-education groups with family caregivers of people diagnosed with a first psychotic episode (ÖKSÜZ et al, 2017) and family caregivers of people diagnosed with bipolar disorder (SAZVAR, 2017) showed that this intervention decreased EE levels. Another study, after implementing a psycho-educational intervention program with family caregivers of people with schizophrenia found its effectiveness in reducing both overload and emotion expressed in the CC component, as well as increasing positive attitudes in the experimental group.…”
Section: Discussionmentioning
confidence: 99%